SUN-336 Obesity and Impaired Glucose Metabolism in Adult Patients with X-Linked Hypophosphatemia - Lecoq, Anne-Lise (J Endocr Soc, 2020)
Background: X-linked hypophosphatemia (XLH) is characterized by increased activity of circulating FGF23 resulting in renal phosphate wasting and abnormal bone mineralization. Epidemiologic studies suggest a relationship between FGF23, obesity and metabolic syndrome. However, the prevalence of metabolic complications in adult XLH patients is not known. Study design: We conducted a prospective cohort study (CNIL 2171036 v 0) in a single tertiary referral center. Subjects: Patients were adult subjects with XLH, defined as hypophosphatemia due to renal phosphate wasting with either documented PHEX mutation (92%) and/or family history of rickets. Healthy controls were selected among adult participants of the AcroCut cohort and matched for sex, age and body mass index (BMI). Methods: Prevalence of obesity and diabetes in patients was compared with the general French population (ObEpi 2012; Bonaldi C. et al., Bulletin épidemiologique hebdomadaire 2016) and prevalence of glucose intolerance in patients, assessed by standard 75-g OGTT, was compared to matched controls. Resistance to insulin was evaluated with HOMA-IR index. Results: 107 patients (79 women and 28 men) were recruited. Median age at evaluation was 35.5 years (range 16.9-74.2) and median BMI was 25 kg/m(2) (range 18-48). Thirty-eight (35.5%) patients were overweight (29 women) and 22 (20.5%) patients were obese (16 women). Distribution of normal weight, overweight and obesity in adult XLH patients differed from that seen in the general French population. We observed an excess of overweight and obesity (+20%, 95% CI [+6; +33], P=0.013) in comparison to general population, especially in younger age categories (under 45 years of age). Three (2.8%) out of the 107 patients were treated for diabetes which did not differ from the expected frequency of type 2 diabetes of 5% in the French population. Twelve (13%) out of 90 patients with available OGTT were glucose intolerant or diabetic compared to ten (12%) of the 82 matched controls (P=0.995). Decreased insulin sensitivity assessed by HOMA-IR was found in fourteen (15.6%) adult XLH patients. Comparison of insulin and glucose curves obtained during the OGTT in patients and matched controls are planned to analyze insulin sensitivity in both populations. Conclusion: Adult XLH patients are prone to develop overweight and obesity, particularly adolescents and young adults. This excess of weight does not seem to result in increased prevalence of metabolic disorders. Insulin sensitivity, yet, needs to be further evaluated in these patients and compared to appropriate controls. FGF23 concentrations will also be assessed to search for determinants of insulin sensitivity in patients. Lifestyle recommendations to prevent obesity, promoting physical activity, are thus essential in the management of XLH patients.